Tingkat Materialitas Berdasarkan Kepentingan Stakeholder pada Penyajian Laporan Keberlanjutan - Alfa Tsurayya Fahira; Nurzi Sebrina (Universitas Negeri Padang, 2024)
This study aims to investigate the level of materiality based on stakeholder importance in sustainability reports. This research will assess whether companies involve stakeholders in the materiality analysis process, what engagement methods are used, what are the most material topics according to stakeholders, and whether the sustainability report implies materiality topics in accordance with stakeholder needs in the presentation of the sustainability report. The population of this study are companies participating in the Asia Sustainability Reporting Rating (ASRRAT) 2020-2022. By using a sampling method, namely purposive sampling, 19 companies with 57 sustainability reports were obtained. Using the content analysis research method with a qualitative approach, this study found that the stakeholders most frequently involved in reporting are customers, employees, communities, governments, and shareholders with Focus Discussion Group (FGD), survey, and questionnaire engagement methods. Meanwhile, the most material topics according to stakeholders are economic performance topics, indirect economic impacts, and anti-corruption topics. On the environmental aspect, energy, water, biodiversity, and emission topics. In the social aspect, employment, occupational health and safety (OHS), training and education, and diversity and equality topics. Overall, the content of the sustainability report is in accordance with material topics according to stakeholder importance. But the company has not presented information on the disclosure of material topics in a complete and detailed way.